Comparison of the Effectiveness of Mindfulness-Based Cognitive Therapy and Acceptance and Commitment Therapy on Pain Anxiety and Self-Compassion in Patients with Breast Cancer in the City of Sari - Nouri Talavaki, Zahra; Fakhri, Mohammad Kazem; Hasanzadeh, Ramzan (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study was conducted with the aim of comparing the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) and Acceptance and Commitment Therapy (ACT) on pain anxiety and self-compassion in patients with breast cancer in the city of Sari.Methods and Materials: The research method was quasi-experimental using a pretest–posttest design with a control group and a three-month follow-up. The statistical population included all women with breast cancer who referred to the Comprehensive Oncology Centers of Imam Khomeini Hospital in Sari in 2025. From this population, 45 individuals were selected through convenience sampling and randomly assigned to two experimental groups and one control group (15 participants in each group). MBCT and ACT sessions were delivered individually in eight 90-minute sessions, once per week. Participants completed the Pain Anxiety Questionnaire developed by McCracken and Dhingra (2002) and the Self-Compassion Scale by Shahabi et al. (2020) during the pretest, posttest, and follow-up stages. The data were analyzed using repeated-measures analysis of variance and Bonferroni post-hoc tests.Findings: The results showed that both MBCT and ACT, compared to the control group, led to improvements in pain anxiety and self-compassion in patients with breast cancer, and this effect remained stable at follow-up (p < .001). However, MBCT was more effective than ACT in significantly increasing self-compassion. In contrast, the difference between the two therapeutic approaches in reducing pain anxiety was not significant (p > .05).Conclusion: According to the findings, MBCT is an effective method for improving self-compassion. However, the effectiveness of the two therapies on pain anxiety was similar. Therefore, these treatments can be considered complementary interventions alongside pharmacological approaches to improve the psychological well-being of these patients.